العلاقة بين الدولة والمجتمع في الجزائر: دراسة في مهددات السِّلْم الإجتماعي - بوقرة, عيسى; ملوكي, سليمان (University of Eloued جامعة الوادي, 2020)
إن إشكالية العلاقة بين الدولة والمجتمع قضية عامة وفعالة في عالمنا المعاصر، فالسِّلم الاجتماعي الذي غدا مطلبا وحاجة تاريخية ملحة لمجتمعات الجنوب، لا يتحقق إلا بإعادة النظر في صميم العلاقة وذلك بتوضيح أبعاده الاقتصادية (التوزيع العادل للدخل) والاجتماعية ( تحقيق السِّلم بين مختلف المكونات الإثنية والطائفية والدينية)، والتي تبقى حاجزا أمام انفراج العلاقة بين الدولة والمجتمع ضمن موقف مجتمعي سلمي . وتتعدد مظاهر العلاقة بين الدولة والمجتمع في الجزائر منذ أحداث أكتوبر 1988 والتي كان لها تأثير كبير على السلم الاجتماعي امتدت آثارها إلى سنوات اتسعت فيها الهوة بين الدولة والمجتمع بحيث انتشر العنف وحالة اللاّأمن وانعدام الاستقرار هذا بالإضافة إلى تدهور الوضعية الاقتصادية وهذا ما يتطلب البحث في إشكالية العلاقة بين الدولة والمجتمع باعتبارها الإشكالية الأم والتي تندرج في نطاقها بحث القضية المدروسة. The problem of the relationship between the state and society is a public and effective issue in our contemporary world, Social peace, has become a demand and an urgent historical need for southern societies, can only be achieved by reconsidering the core of the relationship by clarifying its economic dimensions (equitable distribution of income) and social (achieving peace between the various ethnic, sectarian and religious components), which remains a barrier to the separation of the state/society within A peaceful societal attitude. There are many aspects of the relationship between the state and society in Algeria since the events of October 1988, which had a major impact on social peace. Its effects extended to years in which the gap between the state and society widened, so that violence and instability spread in addition to the deteriorating economic situation, This requires research into the problem of the relationship between the state and society, as the basic and within the scope of which falls the examination of the studied issue.
مجلد11، عدد3
Keywords: السلم الاجتماعي ; الدولة ; المجتمع ; الحركات الاحتجاجية; Social peace ; state ; society ; The protest movements